An Analysis of Administration Fees in Murabâha Financing Case Study: Muamalat Bank of Indonesia, Sragen Branch in 2015 - Fanani, Ahmad; Amrina, Mien (AL- IKTISAB Journal of Islamic Economic Law, 2017)
Administration fee is commonly used for operational activities, which its rate ischarged to customers depends on each bank. It is charged for several products andservices that require certain administrations. Hence, Muamalat Bank is pioneer of Islamicbank in Indonesia founded in 1992 has contributed to the development of product andservice for customers. It has many branches in all districts such as branch Sragen in eastjava. In relation with administration fee, Muamalat Bank, branch Sragen has producedmany contracts by imposing administration fees with in them such as in murâbahafinancing. Finding of the study are that murâbaha financing is imposed for operationaland survey fee. The administration fee in branch Sragen is determined by tiered pricingstructure on murâbaha financing, which is not permissible in Islamic principles becauseit contains element of ghârar and ghaban